Pendekatan Diagnostik Berbasis Extreme Learning Machine dengan Kernel Linear untuk Mengklasifikasi Kelainan Paru-Paru - Winangun, Putu Prima; Widyantara, I Made Oka; Hartati, Rukmi Sari (Majalah Ilmiah Teknologi Elektro, 2020)
Abstract— an expert system can be used as a second opinion for comparison or supporting diagnosis from experts. Data mining is used to obtain information applied to this system. Whereas in conducting learning using Artificial Neural Networks which apply the Extreme Learning Machine method so that it can accelerate learning up to thousands of times. In this paper, software development is carried out to test the activation functions used in conducting learning and the variables used as input during learning.